Formulasi Sediaan Ekstrak Etanol Kulit Buah Alpukat (Persea Americana Mill.) Sebagai Krim Alas Bedak - Hamdhani Hamdhani; Muharni Saputri; Sudewi Sudewi; Linda Margata (Journal of Pharmaceutical and Sciences, 2023)
Background; Avocado (Persea americana Mill.) is a plant that is widely grown in Indonesia. Peel avocado is known to contain secondary metabolites such as flavonoids which are useful as antioxidants. This study aims to determine the peel of avocado (Persea americana Mill.) in the form of ethanol extract can be formulated into a foundation cream preparation which at a certain concentration has antioxidant activity. Method; The study was conducted using an experimental method, using peel avocado test material (Persea americana Mill.) processed by maceration using 96% ethanol extract formulated into a foundation cream preparation in a concentration of 1.5%; 2%; 2.5%; and blank. Examination of the physical quality of the preparation includes homogeneity test, pH test, viscosity test, stability test, irritation test, moisture test and antioxidant activity test. Result; The results showed that the yield of peel avocado (Persea americana Mill.) was 12.99%. All formulations met the requirements of the gel evaluation test with a pH range of 6.0-6.5. After doing the cycling test, it was 5.9-6.2. The viscosity results are 15,250-20,050 mPa.S. All formulations are homogeneous and stable. Formulation 3 has an IC50 value of (54.74µg/mL) in the "strong" antioxidant category and has a % recovery value of 67.23%.